2018
DOI: 10.5607/en.2018.27.3.171
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Kinase Activity Induces Mitochondrial Fission in Microglia via Drp1 and Modulates Neuroinflammation

Abstract: Leucine-rich repeat kinase 2 (LRRK2) mutations are the most common genetic cause of Parkinson's disease (PD). LRRK2 contains a functional kinase domain and G2019S, the most prevalent LRRK2 pathogenic mutation, increases its kinase activity. LRRK2 regulates mitochondria morphology and autophagy in neurons. LPS treatment increases LRRK2 protein level and mitochondrial fission in microglia, and down-regulation of LRRK2 expression or inhibition of its kinase activity attenuates microglia activation. Here, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…Previous studies of microglia have shown that LRRK2 contributes to mitochondrial homeostasis through interaction with the mitochondrial fission protein DRP1 (Ho et al, 2018). Thus, we hypothesized that the loss of Lrrk2 may compromise mitochondrial stability via misregulation of DRP1 activity, leading to fragmented mitochondria and spillage of mtDNA into the cytosol.…”
Section: Defects In Type I Ifn Responses In Lrrk2 Ko Macrophages Are mentioning
confidence: 95%
“…Previous studies of microglia have shown that LRRK2 contributes to mitochondrial homeostasis through interaction with the mitochondrial fission protein DRP1 (Ho et al, 2018). Thus, we hypothesized that the loss of Lrrk2 may compromise mitochondrial stability via misregulation of DRP1 activity, leading to fragmented mitochondria and spillage of mtDNA into the cytosol.…”
Section: Defects In Type I Ifn Responses In Lrrk2 Ko Macrophages Are mentioning
confidence: 95%
“…It has recently been suggested that LRRK2 may promote mitochondrial fission via Drp1 in a kinase-dependent manner, with increased fission due to G2019S-LRRK2 expression resulting in increased TNF-α production in the brains of mice (Ho et al, 2018). Brain lysates of G2019S-LRRK2 knock-in mice exhibited reduced NFkB p50 s337 phosphorylation, decreasing NFkB p50 inhibitory signaling and pro-inflammatory gene transcription, compared to WT mice (Russo et al, 2018).…”
Section: Lrrk2 Expression In Cells Of the Cns And Peripheral Immune Cmentioning
confidence: 99%
“…6.2.1 | Drp1 involve in the mutant leucine rich-repeat kinase 2 (LRRK2)-induced PD LRRK2, a pathogenic gene of PD, has many functions including regulating the transportation of vesicles, the autophagy, oxidative stress, neurotoxicity, and mitochondrial dynamics. It is reported that 13% of familial PD patients and 1-2% of nonfamilial PD patients have mutations in the LRRK2 gene (Ho et al, 2018;Perez Carrion et al, 2018).…”
mentioning
confidence: 99%